Corneal epithelium is altered in keratoconus and forme fruste keratoconus - Nomuundari Sukhee; Hiroyuki Namba; Marie Ikeda; Sera Ichinohasama; Tomoyuki Kurihara; Nene Okamoto; Junko Yoshida; Tomohiko Usui (Scientific Reports)
Abstract This study investigated corneal epithelial thickness and its distribution in keratoconus (KC) and forme fruste keratoconus (FFK). A total of 35 KC eyes, 25 FFK eyes, and 35 control eyes underwent anterior segment-optical coherence tomography for corneal epithelial evaluation. Sixty KC eyes were included for the assessment of epithelial changes according to KC severity. Epithelial thickness in the central, paracentral, and peripheral areas—each subdivided into eight zones—was statistically analysed. Minimum, maximum, and average epithelial thicknesses were reduced in KC eyes, especially in the inferior and inferior-temporal zones. Standard deviations were greater in KC eyes across nearly all zones. In FFK and KC eyes, the differences between superior and inferior epithelial thickness were significantly altered compared to control eyes. According to the Amsler–Krumeich classification, more advanced KC stages were associated with greater corneal thinning. Epithelial heterogeneity decreased in the central and paracentral area as a result of superior epithelial thinning, whereas it increased in the peripheral area with KC progression. Epithelial thickness and distribution were altered in KC and even in FFK eyes with normal topography. Different stages of KC may exhibit distinct epithelial remodelling patterns.